Efficacy and Safety of Intra-Articular Platelet-Rich Plasma in Osteoarthritis Knee: A Systematic Review and Meta-Analysis. (30th April 2021) - Hong, Mao; Cheng, Chongjie; Sun, Xiaowei; Yan, Yan; Zhang, Qidong; Wang, Weiguo; Guo, Wanshou
Abstract : Background . Knee osteoarthritis (KOA) is a common disease in aged adults. Intra-articular (IA) injection of platelet-rich plasma (PRP) therapy is an effective minimally invasive treatment for KOA. We aimed to compare the efficacy and safety of platelet-rich plasma (PRP) with placebo or other conservative treatments. Methods . We conducted a meta-analysis to identify relevant articles from online register databases such as PubMed, Medline, Embase, and the Cochrane Library. The primary outcomes were the visual analogue scale (VAS) score, Western Ontario and McMaster Universities Arthritis Index (WOMAC) score, and International Knee Documentation Committee (IKDC) subjective score. The secondary outcome was the adverse event rate. Results . A total of 895 articles were identified, of which 23 randomized controlled trials that met the inclusion criteria were determined as eligible. Compared with placebo, PRP had a lower VAS score and higher IKDC subjective score at the 6 th month after treatment and significantly less WOMAC score during the follow-up period. Compared with oral NSAIDs, PRP gained a lower WOMAC score at the 6 th month after treatment. The VAS score decreased after treatment when reaching PRP and CS. As compared to the HA, the VAS score, WOMAC score, and IKDC subjective score all revealed better PRP results. There were no significant differences in adverse event rates comparing PRP versus placebo or HA. Different PRP applications did not show significant differences in VAS score in the 1 st month and WOMAC score in the 3 rd month after treatment. Conclusion . To compare with the conservative treatments mentioned above, PRP is more effective in relieving symptoms. There were no significant differences between triple PRP application and single PRP application in short-term curative effect.